UNIVERSAL INTEGRATED SYSTEM SUPPORTED BY THE ORGANIZATION LASER EXPRESS EXPERTISE - L. V. Rudikova (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The main provisions needed for the development of complex internet systems that store, process and analyze data, intended to organize an express laser expertise are presented. With structural software development methodology derived functional model of the system the data model and the general architecture of a universal system that supports the collection, storage and analysis of data related to the materials science expertise and technological research articles, historical and artistic treasures of the environment, biostructures are obtained.